2011
DOI: 10.2106/jbjs.i.01317
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Predictors of Returning to Work Following Primary Total Knee Arthroplasty

Abstract: Although the physical demands of a patient's job have a moderate influence on the patient's ability to return to work following a primary total knee arthroplasty, the patient's characteristics, particularly motivation, play a more important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
88
6
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 31 publications
17
88
6
2
Order By: Relevance
“…These recovery periods are consistent with the general recommendations of the participating surgery centers. Our overall average of time of 9 weeks off work for recovery after TKA is the same as that reported in another American study involving 162 patients undergoing TKA, all of whom were working before surgery and followed prospectively for 6 months after surgery [17]. The percentage of patients in our study who required restrictions after surgery (19%) was similar to those requiring restrictions before TKA (18%).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These recovery periods are consistent with the general recommendations of the participating surgery centers. Our overall average of time of 9 weeks off work for recovery after TKA is the same as that reported in another American study involving 162 patients undergoing TKA, all of whom were working before surgery and followed prospectively for 6 months after surgery [17]. The percentage of patients in our study who required restrictions after surgery (19%) was similar to those requiring restrictions before TKA (18%).…”
Section: Discussionsupporting
confidence: 81%
“…Access to affordable health insurance for many patients is a benefit of employment in the United States and many other countries. In one US study of patients between the ages of 18 and 69 years undergoing TKA, 77% were receiving health insurance through their employer [17]. Although TKA is one of the most commonly and increasingly performed surgical procedures in the world, there is limited information for younger, high-demand patients in regard to return to work ( Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,7 In our analysis, self-employment was also found to be associated with partial or no return to work whereas it was associated with a faster return to work in previous research. 16 It should be noted, however, that, in that study, the speed of return to work was the outcome, regardless the number of working hours. Our finding may be related to the observation that self-employed patients in all likelihood work more hours than wage earners and above the average for fulltime workers (approximately 36-40 hours per week), 17 yielding a larger potential for productivity loss.…”
Section: Discussionmentioning
confidence: 62%
“…Of interest, a recent study found that the physical demands of a patient's job had a moderate influence on the patient's ability to return to work following a primary total knee arthroplasty. However, the authors noted that certain characteristics of the patient, such as a higher preoperative mental composite summary score on the Medical Outcomes Study 12-Item Short-Form Health Inventory Survey (SF-12) and a higher level of motivation (sense of urgency to return), increased the likelihood of return to work 39 . Traditionally, orthopaedists focus on optimal implant material, surgical technique, and postoperative rehabilitation to ensure optimal surgical outcome after total knee replacement.…”
Section: Emotional Health Is Important To Total Knee Replacement Carementioning
confidence: 99%